RAJA YOGA MEDITATION AS INNOVATION OF PREVENTION AND THERAPY IN PEDOPHILIA - Satyarsa, Agung Bagus Sista; Suryantari, Sang Ayu Arta; Baskaranata, Putu Bagus Onicha; Diniari, Ni Ketut Sri (Essential: Essence of Scientific Medical Journal, 2019)
Pedophilia is a frequent case in the world including Indonesia. This makes Indonesia a pedophilia emergency. The data on child abuse based on Commission Child Protection Indonesia (KPAI) in 2010-2014 was increased 42-58 percent of pedophilia. Besides, the victims will eventually become pedophiles that are called victim-to-abuser cycles. Recently, it needed the successful key to therapy against dystonic ego of a pedophilia abuser with Raja Yoga meditation. Meditation is a strategy that has been used to control libidinal (id) and self-regulatory (superego) used in mental health counseling and psychiatry because it can decrease arousal, anxiety, depression, and behavioral disorder. One type of meditation is Raja Yoga meditation that has been studied for years of ability to change behavior and self-regulatory. Supported by several studies, this meditation also can repair abnormalities in the limbic system. Raja Yoga meditation is effective therapy and prevention in pedophilia.